Transaksi cryptocurrency : Bagaimana pandangan hukum ekonomi islam memandang? - Sisca Ferawati Burhanuddin (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
The development of the digital era is increasingly widespread, prompting changes to the payment system, some of which provide convenience, especially in terms of economic activity services. Cryptocurrency is a blockchain-based technology that is often used as a digital currency. Digital money is different from conventional money, this type of money does not have a physical form but only a block of data bound by a hash as validation. Basically cryptocurrency has almost the same function as other currencies, but this currency does not have a physical form like currency in general, although it provides a number of advantages for its users, the existence of cryptocurrency is still a question mark because it does not have officialpermission from the government or from state financial institutions. This research is a type of qualitative research, using a descriptive method while the results of this study explain that Cryptocurrency is a new phenomenon, especially in terms of transactions, the rapid development of technology in the 4.0 revolution era makes humans have to adapt to the various conveniences it presents, but if Seeing the position of cryptocurrency, especially in Indonesia, the government has not officially given permission because it is against the law and is not supervised by financial services authority institutions. Meanwhile, according to Islamic economic law, the concept of cryptocurrency contains gharar and dharar because the inventor or creator is not known for certain, there is no authority to ensure the validity of transactions, has no intrinsic value, and cannot be separated from speculation about the price which is very volatile and is only used as a profit and loss tool. then Cryptocurrency contains elements of Maysir..